Perinatal Mood and Anxiety Disorder Management in Multicenter Community Practices: Clinicians' Training, Current Practices and Perceived Strategies to Improve Future Implementation - Ajeng J. Puspitasari; Dagoberto Heredia; Elise Weber; Hannah K Betcher; Brandon J. Coombes; Ellen M. Brodrick; Susan M. Skinner; Angie L. Tomlinson; Shana S. Salik; Summer V. Allen; Jason S. O'Grady; Emily K. Johnson; et al. (SAGE Publishing, 2021)
Background: This study aimed to explore clinicians' perspectives on the current practice of perinatal mood and anxiety disorder (PMAD) management and strategies to improve future implementation. Methods: This study had a cross-sectional, descriptive design. A 35-item electronic survey was sent to clinicians (N = 118) who treated perinatal women and practiced at several community clinics at an academic medical center in the United States. Results: Among clinicians who provided care for perinatal women, 34.7% reported never receiving PMAD management training and 66.3% had less than 10 years of experience. Out of 10 patients who reported psychiatric symptoms, 47.8% of clinicians on average reported providing PMAD management to 1 to 3 patients and 40.7% noted that they conducted screening only when patient expresses PMAD symptoms. Suggested future improvements were providing training, developing a referral list, and establishing integrated behavioral health services. Conclusions: Results from this study indicated that while PMAD screening and management was implemented, improvements are warranted to meet established guidelines. Additionally, clinicians endorsed providing PMAD management to a small percentage of perinatal patients. Suggested strategies to increase adoption and implementation of PMAD management should be explored to improve access to behavioral health services for perinatal women.